POPULATION FLUCTUATION OF NATURAL ENEMIES OF STEM BORER, Chilo partellus IN MAIZE - G. V. SUNEEL KUMAR (The Journal of Research ANGRAU, 2018)
Experiments were carried out during four seasons viz., Kharif, 2014, Rabi 2014-15, Kharif, 2015 and Rabi 2015-16 to evaluate the population fluctuation of stem borer and natural enemies in maize crop. The highest stem borer infestation during Kharif season with mean population of 2.86 larvae / plant was recorded during 40th standard week coinciding with grain filling stageof maize. While during Rabi season, peak larval population of C. partellus (2.42 larvae / plant) was noticed during 4th standard week coinciding with flowering and fertilization (silking) stage of maize. Peak incidence of Coccinella transversalis Fab. and Cheilomenus sexmaculata Fab. during Kharif season was noticed in 41st standard week (0.84 and 0.72 beetles per plant, respectively), while during Rabi, peak population of C. transversalis in 2nd and 3rd standard weeks (0.34 beetles per plant) and C. sexmaculata in 4th standard week (0.78 beetles / plant). Peak activity of spiders was found to follow the same trend during kharif with 1.22 per plant in 41st standard week and 0.89 per plant during rabi in 4th standard week. Peak parasitism by Cotesia flavipes was found during 40th standard week (25.12 %) in Kharif and 4th standard week (10.8%) in Rabi coinciding with peak larval population of the maize stem borer. C. flavipes showed positive and significant correlation with larval population of C. partellus on average basis of both study years of Kharif (r = 0.940) and Rabi (r = 0.868) seasons